(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Analysis of Factors Affecting the Decision to Purchase Organic Rice Products at PT Bali Organik Internasional. PT Bali Organik Internasional is engaged in agriculture including the management, marketing and distribution of agricultural products and organic plantations, one of which is organic rice. This research aims to analyze the factors that influence the decision to buy organic rice. This research targets consumers of organic rice products of PT Bali Organik Internasional. Sampling is carried out using a method, namely nonprobability sampling using the accindental sampling technique. Data analysis in this study is by using Structural Equation Modelling – Partial Least Square (SEM–PLS) using Partial Least Square (PLS) technique with formative constructive properties using warp–PLS 7.0 software. From the results of SEM- PLS analysis, it was obtained that the product criterion variable (X1) with a p-value of 0.009 has a strong significant influence on the purchase decision (Y). The marketing variable (X2) with a p-value of 0.037 has a significant influence on the purchase decision (Y). The consumer awareness variable (X3) with a p- value of 0.002 has a strong significant influence on the purchase decision (Y).